2016
DOI: 10.1080/02640414.2016.1232488
|View full text |Cite
|
Sign up to set email alerts
|

Revealing the decision-making of dribbling in the sport of futsal

Abstract: This study aimed to investigate why futsal players decide to dribble. For this purpose, we analysed 396 trials comprising the dribbles (n = 132), passes (n = 131) or shots (n = 133), performed by 70 male futsal players. Passing and shooting angles, and interpersonal distance, including their rates of change (velocity and variability), were regarded as measures of interpersonal coordination tendency and a comparison was made among dribbling, passing and shooting situations. In addition, the variables identified… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
33
0
13

Year Published

2017
2017
2024
2024

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 37 publications
(53 citation statements)
references
References 14 publications
4
33
0
13
Order By: Relevance
“…Interestingly, most studies in ecological dynamics have investigated players' decisionmaking in such invasive team sports such as basketball (Araújo, Davids, Bennett, Button, & Chapman, 2004;Cordovil et al, 2009), rugby (Correia et al, 2012;Passos, Cordovil, Fernandes, & Barreiros, 2012), futsal (Corrêa et al, 2016;Travassos, Araújo, Duarte, & McGarry, 2012) and soccer (Duarte et al, 2012;Romero, Denardi, Travassos, & Corrêa, 2016). An important point here is that the ways in which players interact in terms of opposing and cooperating in these team sports are different from those of net team sports such as volleyball.…”
Section: Introductionmentioning
confidence: 99%
“…Interestingly, most studies in ecological dynamics have investigated players' decisionmaking in such invasive team sports such as basketball (Araújo, Davids, Bennett, Button, & Chapman, 2004;Cordovil et al, 2009), rugby (Correia et al, 2012;Passos, Cordovil, Fernandes, & Barreiros, 2012), futsal (Corrêa et al, 2016;Travassos, Araújo, Duarte, & McGarry, 2012) and soccer (Duarte et al, 2012;Romero, Denardi, Travassos, & Corrêa, 2016). An important point here is that the ways in which players interact in terms of opposing and cooperating in these team sports are different from those of net team sports such as volleyball.…”
Section: Introductionmentioning
confidence: 99%
“…instead, previous research has investigated only isolated specific motor skills, e.g. kicking, dribbling, and ball control [10,12,13,19].…”
Section: Discussionmentioning
confidence: 99%
“…However, prior studies have focused on evaluating adolescent futsal players over the course of sports development, i.e., between 12 and 17 years of age [12,13]. Thus, scientific studies are ignoring how players perform specific motor skills between 6 and 11 years, a crucial moment of motor learning phase [14,15], besides focusing only on the execution of offensive actions, neglecting the defensive results of the players.…”
Section: Introductionmentioning
confidence: 99%
“…Understanding how performance emerges in complex systems like futsal is to understand how different players with different capabilities (physiological, tactical, technical) interact under task (game rules, different game systems) and environment (home-away, winning losing teams) constraints to make emerge functional, dyadic and collective spatiotemporal patterns of relations between teammates and with opponents . In the past years, grounded on the main ideas of complex systems a lot of works (Travassos et al, 2012a;Vilar et al, 2013;Corrêa et al, 2016) have been developed, through the use of positional data, with the aim to capture the informational constraints that guide players and teams tactical behaviours and also the emergent patterns of coordination that characterizes and sustain teams' performance in futsal. Such research have identified interesting spatial-temporal relations between players' distances, angles, spaces covered or alignments with the goal, or the ball that help coaches to really understand the tactical behaviours of players and teams based on the coach model developed.…”
Section: Discussionmentioning
confidence: 99%